Clinical, Infection Rate and Conventional Identification of Cryptosporidium spp. in Children , Lambs and Goat Kids - Enaad, Duha Faisal; Minnat, Tareq Rifaaht; Hussian, Haleem Hamza (Diyala Journal for Veterinary Sciences, 2023)
Background: Cryptosporidiosis is considered to be a dangerous zoonotic infection brought on by a protozoan parasite with detrimental economic and public health repercussions on both humans and animals. Aims: The study aimed to clinical, infection rate and identification with morphological characterization of Cryptosporidium spp from Children, lambs and kids. Material and Methods: A total of 200 fecal samples was collected from 100 children, 65 lambs and 35 goat kids from different regions in Diyala governorate, were collected from September 2022 to May 2023 and traditional techniques (Sheather’s flotation technique, modified ziehl-neelsen staining microscopic examination) were used to check for Cryptosporidium spp. infection. Results: Clinical symptoms of cryptosporidium infection in 53 lambs and 15 goat kids included watery diarrhea, anorexia, sadness, abdominal discomfort, and weight loss. As a result, it was determined that the total infection rate was 45.5% (89/200), which was made up of 81.5% (53/65) in lambs, 42.9% (15/35) in goat kids, and 21% (21/100) in children. There was a significant difference (P <0.05) in the infection rate of cryptosporidiosis between sexes, as shown by high infection in males (72.7%), females (65%) and goat kids, respectively, in the age groups of less than 3 months (66.7%), more than 3 months (51.4%), and less than 3 months (40.0%). Regarding the area, the majority of infected children lived in the rural area at a ratio of 27.7%, followed by the urban area at a ratio of 13.04%. Further analysis of the relationship between study months and infection rates revealed that the highest infection rates 33.3%, 62.5%, and 66.7% were seen in November, while the lowest infection rates 5%, 50%, and 33.3% were observed in May, in Children, lambs, and kids, respectively. Conclusion, this study showed the significance of Cryptosporidium in lambs as opposed to youngsters and children, where a high infection rate and the relationship between sex, age groups, system houses, and months of study had a major impact on the infection rate of Cryptosporidiosis.